Efficacy of Laparoscopic Surgery Combined With Leuprorelin in the Treatment of Endometriosis Associated With Infertility and Analysis of Influencing Factors for Recurrence - Yu, Lu; Sun, Yunming; Fang, Qiongyan (Frontiers in Surgery, 2022)
Objective To explore the curative effect of laparoscopic surgery combined with leuprorelin in the treatment of endometriosis with infertility and the related factors of recurrence after treatment. Methods A total of 158 patients with endometriosis and infertility were selected in our hospital from January 2019 to June 2020. Patients were randomly divided into the control group and the observation group, with 79 patients in each group. Patients in the control group was treated by laparoscopy surgery combined with dydrogesterone, while those in the observation group was treated with laparoscopic surgery combined with leuprorelin. The hormone levels, recurrence rate, pregnancy rate and adverse reaction of the two groups were compared. Combined with clinical and pathological information, the related factors of postoperative recurrence were analyzed. Results After treatment, the levels of luteinizing hormone, follicle-stimulating hormone and estradiol in the observation group were lower than those in the control group (P < 0.05). The recurrence rate at 12 months after operation in the observation group was lower than that in the control group, and the pregnancy rate was higher than that in the control group (P < 0.05). However, there was no significant difference in the incidence of adverse reactions between the two groups (P > 0.05). Preoperative dysmenorrhea was an independent risk factor for postoperative recurrence in patients with endometriosis, and postoperative pregnancy was a protective factor for postoperative recurrence in patients with endometriosis (P < 0.05). Conclusion Laparoscopy combined with leuprorelin in the treatment of endometriosis with infertility can improve hormone levels, increase the pregnancy rate and reduce the recurrence rate. Preoperative dysmenorrhea is an independent risk factor for postoperative recurrence, which should be quantified and included in the recurrence risk prediction model. Postoperative pregnancy can reduce the recurrence rate after operation, and patients with fertility requirements should be encouraged to make activ preparations for postoperative pregnancy.